The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/gme.0000000000001578
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and fear of death in postmenopausal women

Abstract: Objective: This study aimed to determine the frequency of depression in postmenopausal women, examine some variables that are thought to be related, and evaluate the relationships between postmenopausal depression, anxiety, and fear of death. Methods: The study is a cross-sectional study conducted among postmenopausal women who applied to an Obstetrics and Gynecology Polyclinic in Sakarya, Turkey, between March and September 2018. The study group consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
1
16
1
2
Order By: Relevance
“…17 In a study conducted on postmenopausal women in Turkey, the prevalence of depression was reported as 41%. 28 Although the incidence of depression in our study was lower than in China and higher than in the rest of the world, it was similar to the prevalence of depression in premenopausal and postmenopausal periods. The different results reported in various studies include the non-standardisation of the diagnostic methods used in the studies and the other socio-economic and cultural characteristics of the people who make up the study populations.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…17 In a study conducted on postmenopausal women in Turkey, the prevalence of depression was reported as 41%. 28 Although the incidence of depression in our study was lower than in China and higher than in the rest of the world, it was similar to the prevalence of depression in premenopausal and postmenopausal periods. The different results reported in various studies include the non-standardisation of the diagnostic methods used in the studies and the other socio-economic and cultural characteristics of the people who make up the study populations.…”
Section: Discussionsupporting
confidence: 54%
“…In a database‐based study in Australia, depressive symptoms ranged between 22% and 25% 17 . In a study conducted on postmenopausal women in Turkey, the prevalence of depression was reported as 41% 28 . Although the incidence of depression in our study was lower than in China and higher than in the rest of the world, it was similar to the prevalence of depression in premenopausal and postmenopausal periods.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…GABA reduction has been observed in perimenopausal and postmenopausal women (Wang et al, 2016(Wang et al, , 2019, which correlates with higher FM prevalence in women and its connection with climacteric symptoms (Carranza-Lira & Hernandez, 2014). From this point of view, FM seems to be part of a series of neurological disorders showing perimenopausal prevalence and correlation with gonadal hormone alterations, such as migraine, central vestibular problems, anxiety, and depression (Loder et al, 2007;Mucci et al, 2018;Ozdemir et al, 2020). Various interrelationships between steroid hormones and the GABAergic function have emerged from different studies.…”
Section: A D B E C Fmentioning
confidence: 99%
“…В недавнем кросс-секционном исследовании с участием 485 женщин 35-78 лет в постменопаузе факторами риска развития депрессии у женщин в постменопаузе были признаны смерть партнера или развод; употребление алкоголя; любое заболевание, требующее постоянного приема лекарственных препаратов; наличие каких-либо физических недостатков; психические расстройства в анамнезе, а также, что интересно, совместное проживание с 4 и более детьми [34].…”
Section: неэндокринные факторы риска / Non-endocrine Risk Factorsunclassified